The determinants of bank net interest margins: A panel evidence from South Asian countries - Islam, Md. Shahidul; Nishiyama, Shin-Ichi (Research in International Business and Finance, 2016)
Yearly average net interest margins (%) in South Asian countries. This paper studies the determinants of net interest margins of banks (NIMs) in four South Asian countries (Bangladesh, India, Nepal and Pakistan) in the period 1997–2012 using panel data of 230 banks. The study is in line of Ho–Saunders (1981) dealership model and its later expansions but extended the model by adding new variable the relative size of the banks and also classifying the determinants of interest margins as bank specific, industry specific and macroeconomic specific variables. We found that liquidity and equity positions, required reserve and operating expenses to total asset ratios affect net interest margins positively while relative size of the banks, market power and economic growth affect inversely.